Pengaruh Kualitas Perangkat Desa Terhadap Kualitas Laporan Keuangan Desa - Wahyudi, Agus; Hasri, Diah Anggeraini (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study aims to examine the effect of the quality of village officials on the quality of village financial reports at the village government in Utan District, Sumbawa Regency. This type of research is quantitative research with an associative approach. The data collection technique is using a questionnaire. The number of samples in this study amounted to 36 respondents consisting of the village head, the head of the village consultative body, the village secretary, and the village treasurer. The results showed that the quality of village officials had a positive and significant effect on the quality of village financial reports, with the existence of quality village officials it would produce quality financial reports. The results of the determination test showed that 58.2% of the village financial report quality variables could be explained by the village apparatus quality variable, the rest was influenced by other variables that were not included in this study.